A panel of human neutralizing mAbs targeting SARS-CoV-2 spike at multiple epitopes - Tal Noy-Porat (Nature Portfolio, 2020)
Here, Noy-Porat, Makdasi et al. report the isolation of a panel of neutralizing mAbs selected against SARS-CoV-2 receptor-binding domain (RBD) from a phage display library constructed based on patient samples collected in the acute phase of the disease, which show efficient neutralizing activities against authentic virus in vitro.